Adjectival structures in Romanian New Testament versions - Andreea-Diana POPA SAVU (Diversitate si Identitate Culturala in Europa)
The main objective of this paper is to present the historical evolution of the adjectival subsystem in the written Romanian language, as it is reflected in the most representative Romanian religious texts from the time period between the 17th century and the 20th century. The conclusions refer to the permanent interweaving of the Romanian literary language with the special language of the church, to the development of both functional variants. They have influenced each other, imposing forms that have acquired viability and standardised use, not without possibilities of stylistic and pragmatic nuancing, in various other registers, levels, styles. In other words, the essence of our research has been to recompose the moving, i.e., diachronic, picture of the Romanian adjectival subsystem within the general Romanian language system.